Active Cycle Breathing Exercise on Post Tuberculosis Bronchiectasis - Ricky Gustian Halim; Siti Chandra Widjanantie; Selly C Anggoro (Indonesian Journal of Physical Medicine & Rehabilitation, 2018)
Introduction: Tuberculosis (TB) has remained as a major global health issue in Indonesia. Bronchiectasisfrequently occurs in healing process, followed by excessive phlegm and low physical activity.Methods: A case presentation of 49 years old female diagnosed as bronchiectasis post tuberculosis,difficulty to clear the phlegm, and inactive. Patient has undergone pulmonary rehabilitation by activecycle breathing exercise, 5 days a week, 30 minute/session, for 2 weeks.Results: There was no dyspnea, patient easily remove phlegm, and can be more active, after cyclebreathing exercise program.Conclusion: Active cycle breathing exercise effective to relieve dyspnea, improving patient ability toclearance the phlegm, and increase physical activity.Keywords: Bronchiectasis, active cycle breathing exercise, phlegm clearance, physical activity